Peer Observation Reports and Student Evaluations of Teaching: Who Are the Experts? - Ackerman, David; Gross, Barbara L.; Vigneron, Franck (Alberta Journal of Educational Research, 2009)
This study is an exploratory inquiry into the perceptions of university faculty regarding two forms of teaching evaluations, student evaluations of teaching (SET), and peer observation reports (POR). Which, if either, better assesses the quality of instruction? Who are the real experts in judging teaching quality: peers who are experts in their field or students who are the recipients of instruction? Results suggest that it is better not to rely on a single source of information as evidence of teaching effectiveness. SET and POR provide complementary information from differing perspectives. Advantages and disadvantages of both are discussed.